2011
DOI: 10.1007/s00038-011-0298-9
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in therapeutic treatment during cardiac inpatient rehabilitation in Germany

Abstract: While the latter difference might be in line with the needs of different socio-economic groups, most differences are unlikely to be tailored to patients' needs. Potential causes of inequalities in service provision like structural factors and aspects of the doctor-patient encounter should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…AMI recurrences are clear indicators of disease severity and incompliance with secondary prevention, as well as strong predictors of HF. This finding is in line with previous reports showing poorer adherence to prescribed medications upon discharge 27,28 and lower participation rates in rehabilitation programmes 29,30 among patients with lower compared to those with higher education.…”
Section: Discussionsupporting
confidence: 93%
“…AMI recurrences are clear indicators of disease severity and incompliance with secondary prevention, as well as strong predictors of HF. This finding is in line with previous reports showing poorer adherence to prescribed medications upon discharge 27,28 and lower participation rates in rehabilitation programmes 29,30 among patients with lower compared to those with higher education.…”
Section: Discussionsupporting
confidence: 93%
“…While reporting of effect sizes varied considerably in this sample, examining a subset of studies within the three most commonly reported behaviors can begin to provide an estimate. Looking within studies demonstrating a negative impact of lower SES using multivariate modeling and SES as a dichotomous variable (lower vs. higher), odds ratios ranged from 0.27 to 0.80 (median 0.43) for smoking cessation (3537), 0.12 to 0.40 (median 0.25) for CR attendance (8, 3840), and 0.30 to 0.79 (median 0.56) for medication adherence (41–43). …”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, the included studies on socioeconomic inequity in medical care and mortality in ACS patients found that patients with lower SEP more often presented with risk factors such as smoking, physical inactivity, and high blood pressure; which to some extent accounted for the socioeconomic inequity in reperfusion therapy or CAG, cardiovascular pharmacotherapy, CR, and mortality among the ACS patients [80,89,90,152]. However, other studies found that adjusting for smoking status did not remarkably change effect estimates [63] and patient risk factors could not explain the socioeconomic inequity in reperfusion therapy or CAG of ACS patients [136,217].…”
Section: Discussionmentioning
confidence: 99%
“…However, the present review included a large amount of literature, published within the last decade, which included insignificant and contrary results e.g. from smaller studies on medical care and mortality among ACS patients [101,102,113,114,152]. Due to the attention on socioeconomic inequity in health, we expect studies with insignificant results regarding this topic have a relatively high chance of being published.…”
Section: Strength and Limitationsmentioning
confidence: 99%